85.4k views
6 votes
20 POINTS!! What would be the first step to solve this equation?

m - 13 = 24

A. Subtract 13 from both sides
B. Add 24 to both sides
C. Add 13 to both sides
D. Divide by 13 on both sides

1 Answer

4 votes

Answer:

C. Add 13 to both sides of the equation.

Explanation:

Note the equal sign, what you do to one side, you do to the other. Isolate the variable, m. Add 13 to both sides of the equation:

m - 13 = 24

m - 13 (+13) = 24 (+13)

m = 24 + 13

m = 37

~

User Leonardo Gonzalez
by
5.3k points